Control of scabies in a tribal community using mass screening and treatment with oral ivermectin -A cluster randomized controlled trial in Gadchiroli, India. - Priyamadhaba Behera; Hrishikesh Munshi; Yogeshwar Kalkonde; Mahesh Deshmukh; Abhay Bang (Public Library of Science (PLoS), 2021)
Background Scabies is often endemic in tribal communities and difficult to control. We assessed the efficacy of a community-based intervention using mass screening and treatment with oral ivermectin in controlling scabies. Methods/ findings In this cluster randomised controlled trial, 12 villages were randomly selected from a cluster of 42 tribal villages in Gadchiroli district. In these villages, trained community health workers (CHWs) conducted mass screening for scabies. The diagnosis was confirmed by a physician. Six villages each were randomly allocated to the intervention and usual care arm (control arm). In the intervention arm (population 1184) CHWs provided directly observed oral ivermectin to scabies cases and their household contacts. In the usual care arm (population 1567) scabies cases were referred to the nearest clinic for topical treatment as per the standard practice. The primary outcome was prevalence of scabies two months after the treatment. Secondary outcomes were prevalence of scabies after twelve months of treatment and prevalence of impetigo after two and twelve months of treatment. Outcomes were measured by the team in a similar way as the baseline. The trial was registered with the clinical trial registry of India, number CTRI/2017/01/007704. In the baseline, 2 months and 12 months assessments 92.4%, 96% and 94% of the eligible individuals were screened in intervention villages and 91.4%, 91.3% and 95% in the usual care villages. The prevalence of scabies in the intervention and usual care arm was 8.4% vs 8.1% at the baseline, 2.8% vs 8.8% at two months [adjusted relative risk (ARR) 0.21, 95% CI 0.11-0.38] and 7.3% vs 14.1% (ARR 0.49, 95% CI 0.25-0.98) at twelve months The prevalence of impetigo in the intervention and usual care arm was 1.7% vs 0.6% at baseline, 0.6% vs 1% at two months (ARR 0.55, 95% CI 0.22-1.37) and 0.3% vs 0.7% at 12 months (ARR 0.42, 95% CI 0.06-2.74). Adverse effects due to ivermectin occurred in 12.1% of patients and were mild. Conclusions Mass screening and treatment in the community with oral ivermectin delivered by the CHWs is superior to mass screening followed by usual care involving referral to clinic for topical treatment in controlling scabies in this tribal community in Gadchiroli.